Evaluation of Instant Pounded Yam Flour Produced from Yellow Yam (Dioscorea Cayenensis) - V., Olumurewa J. A.; A., Alejolowo I. (Canadian Journal of Agriculture and Crops, 2019)
This study was aimed at determining the chemical, pasting, functional and organoleptic properties of instant pounded yam flour (IPYF) produced from Dioscorea cayenensis. Fresh yams obtained from a market in Akure, Ondo State, Nigeria, were peeled, washed, sliced to 2, 4 and 6 mm thicknesses with FUTA Slicer. A half portion was blanched at 90 °C and other at 100 °C for 10, 15 and 20 minutes, drained, dried using hot air oven at 60 °C and the dried chips were milled, sieved and package in white polythene bag. Control samples were prepared using Dioscorea rotundata. The samples were analysed for physicochemical, functional, pasting, minerals and organoleptic properties. All data obtained were subjected to statistical analysis. The result of the study showed that IPYF produced from Dioscorea cayenensis had significant higher values in all parameters than the once from Dioscorea rotundata, except in fat, dispersibility and organoleptic properties. It indicates that, Dioscorea cayenensis has good qualities than Dioscorea rotundata when processed to IPYF based on physicochemical, functional and pasting properties. IPYF of 4 mm at 100 oC for 10 minutes is recommended from yellow yam.